2014
DOI: 10.1158/0008-5472.can-13-2679
|View full text |Cite
|
Sign up to set email alerts
|

Recent Prediagnostic Aspirin Use, Lymph Node Involvement, and 5-Year Mortality in Women with Stage I–III Breast Cancer: A Nationwide Population-Based Cohort Study

Abstract: Lymph node-positive breast tumors are more likely to express COX-2 than node-negative tumors. In preclinical studies, COX2 inhibition prevents breast tumor spread to lymph-nodes. Therefore, we examined the association between recent (1 year) pre-diagnostic use of aspirin (COX1/COX2 inhibitor), lymph node involvement at breast cancer diagnosis and breast cancer-specific mortality. Women with stage I-III breast cancer diagnosed from 2001-2006 (N=2,796) were identified from Ireland's National Cancer Registry. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
45
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 36 publications
(55 citation statements)
references
References 54 publications
(61 reference statements)
6
45
4
Order By: Relevance
“…Taken together, our study thus provides a scientific rationale for combining aspirin with standard chemotherapy for successful targeting of both CSC and NSCC pool to restrain the acquisition of aggressive phenotype by breast cancer cells during the course of chemotherapy. These data corroborated previous clinical studies with breast cancer patients, in which a link between aspirin use and lower incidences of cancer initiation, recurrence, and metastasis, the three attributes associated with CSCs, has been found (16,17,48,49).…”
Section: Discussionsupporting
confidence: 91%
“…Taken together, our study thus provides a scientific rationale for combining aspirin with standard chemotherapy for successful targeting of both CSC and NSCC pool to restrain the acquisition of aggressive phenotype by breast cancer cells during the course of chemotherapy. These data corroborated previous clinical studies with breast cancer patients, in which a link between aspirin use and lower incidences of cancer initiation, recurrence, and metastasis, the three attributes associated with CSCs, has been found (16,17,48,49).…”
Section: Discussionsupporting
confidence: 91%
“…However, the authors acknowledged it is likely that patients who remained on aspirin had a more favorable prognosis than those who did not. In a prior study by our group, regular pre-diagnostic aspirin use was associated with a statistically significant reduction in the risk of presenting with lymph node metastasis at the time of diagnosis (27). Similarly, in their meta-analysis of randomized trials, Rothwell and colleagues (2) also found that daily aspirin use, before a cancer diagnosis, was associated with a statistically significant reduction in the risk of presenting with distant metastasis at diagnosis (2).…”
Section: Discussionmentioning
confidence: 73%
“…However, all of these studies included women who commenced aspirin use prediagnosis and continued afterwards, and because of this it is not possible to conclude from their analyses the magnitude of effect attributable to post-diagnostic use alone. There have also been a small number of observational studies examining pre-diagnostic aspirin use and breast cancer outcomes (4,27). Again, however, because pre-and post-diagnostic aspirin use is strongly correlated, it is unclear from these studies what time period of exposure may be most relevant.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in a cohort of stage I-III patients diagnosed in Ireland, aspirin use (predominantly low-dose) in the year prior to diagnosis was associated with a weak nonsignificant reduction in breast cancer mortality (HR 0.80, 95% CI 0.62, 1.04) [33]. In a further study of 935 breast cancer patients enrolled in the Carolina Breast Cancer Study, increased duration and regularity of self-reported pre-diagnostic NSAID use (including aspirin) was associated with reduced breast cancer-specific mortality in women with ERpositive tumours while no association was seen for women with ER-negative tumours [34].…”
Section: Discussionmentioning
confidence: 78%